2021
DOI: 10.3122/jabfm.2021.03.200566
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Burnout, and Other Types of Emotional Distress Among Family Medicine Physicians: Results From a National Survey

Abstract: The study participants completed an anonymous, 30-item survey measuring loneliness, burnout, symptoms of depression, fatigue, in addition to providing demographic information.Results: The response rates were 16.3% (401 of 2456) for all the physicians, 7.0% (113 of 1606) for the AAFP NRN member physicians, and 33.9% (288 of 850) for the AAFP member insight physicians. The prevalence of loneliness, burnout, and depressive symptoms was 44.9% (165 of 367), 45.1% (181 of 401), and 44.3% (163 of 368) respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In a study involving 401 family doctors, the incidence of loneliness was 44.9%. The analysis of the results showed that physicians who experienced a greater sense of loneliness more often reported at least one of the symptoms of occupational burnout [ 11 ]. In other studies, loneliness has been identified as one of the leading stressors in the work of nursing managers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 401 family doctors, the incidence of loneliness was 44.9%. The analysis of the results showed that physicians who experienced a greater sense of loneliness more often reported at least one of the symptoms of occupational burnout [ 11 ]. In other studies, loneliness has been identified as one of the leading stressors in the work of nursing managers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is related to seniority. Doctors with more experience were less likely to see themselves as lonely [ 11 ]. The aim of our study was to look at the phenomenon of occupational burnout in connection with the loneliness and complaining.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the observation that those who lived alone were more depressed ( p = 0.075), we hypothesize that social isolation could have negatively impacted trainees' mental health. A survey conducted prior to the pandemic revealed that loneliness, which correlated with depression, burnout, and fatigue, was common among physicians (Ofei‐Dodoo et al, 2021 ). The thematic analysis additionally identified the negative impact the pandemic has had on socializing and networking.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unprecedented connectivity offered by technological advances, work environments in which physicians practice medicine are paradoxically becoming lonelier, with less face-to-face contact and fewer informal conversations with colleagues [ 1 ]. Nonetheless, even before the pandemic, in a 2019–2020 survey of US family physicians, close to 45% identified as feeling lonely, with significant associations with depression and burnout [ 2 ]. Physician loneliness is on the rise, negatively impacting not only physician well-being [ 2 , 3 ], but also performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, even before the pandemic, in a 2019–2020 survey of US family physicians, close to 45% identified as feeling lonely, with significant associations with depression and burnout [ 2 ]. Physician loneliness is on the rise, negatively impacting not only physician well-being [ 2 , 3 ], but also performance [ 2 ].…”
Section: Introductionmentioning
confidence: 99%